Product Liability, Research and Development, and Innovation - Viscusi, W. Kip; Moore, Michael J. (Journal of Political Economy, 1993)
Product liability ideally should promote efficient levels of product safety, but misdirected liability efforts may depress beneficial innovations. This paper examines these competing effects of liability costs on product R & D intensity and new product introductions by manufacturing firms. At low to moderate levels of expected liability costs, there is a positive effect of liability costs on product innovation. At very high levels of liability costs, the effect is negative. At the sample mean, liability costs increase R & D intensity by 15 percent. The greater linkage of these effects to product R & D rather than process R & D is consistent with the increased prominence of the design defect doctrine.